Walter Hallstein: The Forgotten European?
XVII, 260 p.
Keywords: Walter Hallstein was among the great European visionaries. This is the first book length study of one of the key shapers of the European Community in its early years. The range of contributors include those who worked with Hallstein and have personal recollections of him, and younger historians drawing upon documents only recently available. The book contains sections on his contribution as State Secretary to post-war German foreign policy, his seminal role as the first President of the Commission of the EEC and the legacy of his work and ideas and later years as President of the European Movement.